Bictegravir Plus Tenofovir Alafenamide Nanoformulation as a Long-Acting Pre-Exposure Prophylaxis Regimen: Application of Modeling to Design Non-Human Primate Pharmacokinetic Experiments - Perazzolo, Simone; Mandal, Subhra; Prathipati, Pavan K.; Destache, Christopher J. (Frontiers in Pharmacology, 2020)
Bictegravir (BIC) and tenofovir alafenamide fumarate (TAF), two potent anti-HIV drugs, had been nanoformulated (nBIC-TAF) to achieve once-a-month PrEP coverage. In-vivo mouse experiments for nBIC-TAF exhibited favorable subcutaneous (SC) pharmacokinetics. To probe the clinical suitability of the nBIC-TAF, as the next step, we intend to study nBIC-TAF in non-human primates (NHP), as the best preclinical model to foster clinical trials. Before entering an expensive NHP study, however, we seek to improve our a priori understanding about nBIC-TAF in higher species, having just mouse data. The mechanism-based pharmacokinetic modeling (MBPK) has been used as an appropriate method for pharmacokinetic modeling and interspecies scaling for nanoformulations. Via the use of MBPK, in this work, we created a model for nBIC-TAF able to predict plasma concentration-time curves in NHP. BIKTARVY is a daily oral combination of BIC, TAF and emtricitabine (Gilead Science, CA), approved for HIV therapy. Using BIKTARVY equivalent dosages (from their NHP studies), we predicted that, following just one SC dose of nBIC-TAF in NHP, both BIC and tenofovir will have detectable and above in-vitro efficacy levels for 28 days. Furthermore, the MBPK was able to provide a mechanistic explanation regarding the long-acting mechanism characterizing nBIC-TAF: nanoparticles stores in the SC space from which drugs slowly dissociate. Dissociated drugs in the SC space then buffer the plasma pool over time, yielding an extended-release effect in the plasma. Overall, we predicted for nBIC-TAF a promising long-acting pharmacokinetic in NHP, potentially usable as monthly PrEP. These results will help investigators to gain confidence for facing regulatory submissions at early stages.